Notes on the Rubiaceae. 3. Five new records for Bangladesh (Bangladesh Journal of Botany, 2011)
Critical examinations of some unnamed specimens of the family Rubiaceae collected from Sylhet, Chittagong, Cox’s Bazar and Rangamati districts confirmed the identification of five species which have not been previously recorded from Bangladesh. These species are: Argostemma sarmentosum Wall., Mussaenda incana Wall. ex Roxb., Mycetia mukerjiana Deb & Dutta, Oxyceros rugulosus (Thwaites) Tirveng. and Tarenna helferi (Kurz) N.P. Balakr. The genus Argostemma Wall. is also a new record for Bangladesh. These species are described and illustrated along with ecology, geographical distribution and occurrence. Key words: New records; Rubiaceae; Bangladesh DOI: 10.3329/bjb.v39i2.7482 Bangladesh J. Bot. 39(2): 215-222, 2010 (December)